2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27060
|View full text |Cite
|
Sign up to set email alerts
|

Writing to Learn Engineering: Identifying Effective Techniques for the Integration of Written Communication into Engineering Classes and Curricula (NSF RIGEE project)

Abstract: As engineering continues to grow as a global career, effective communication in the form of technical writing becomes more essential. Professional engineering organizations and universities continually list the ability to communicate technical information as a highly sought attribute in recently-graduated engineers. Unfortunately, numerous logistical challenges prevent many programs from implementing extensive technical writing education within the engineering curriculum. These challenges include budgetary con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…2 Many studies have more generally identified a persistent "competency gap" associated with communication skills, with the capabilities of engineering graduates often falling well below what is sought by the organizations hiring them. 3,4,5 To shed further light on the current state of writing in engineering degree programs, this project surveyed instructional staff in engineering programs at multiple universities to investigate : 1) their attitudes about the current state of writing in engineering classes and writing skills in students, 2) challenges they encounter when trying to incorporate writing, and 3) resources they believe would most help improve the teaching of writing in engineering courses and curricula.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many studies have more generally identified a persistent "competency gap" associated with communication skills, with the capabilities of engineering graduates often falling well below what is sought by the organizations hiring them. 3,4,5 To shed further light on the current state of writing in engineering degree programs, this project surveyed instructional staff in engineering programs at multiple universities to investigate : 1) their attitudes about the current state of writing in engineering classes and writing skills in students, 2) challenges they encounter when trying to incorporate writing, and 3) resources they believe would most help improve the teaching of writing in engineering courses and curricula.…”
Section: Introductionmentioning
confidence: 99%
“…However, if there is empirical evidence that writing enhances academic performance more than when students self-study, it becomes a strong reason to adopt writing in classrooms along with its additional educational bene ts. 11 One of the most important educational bene ts is that writing helps students develop higher-order thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…If the grasp on a certain topic is tenuous, it is difficult to provide descriptions that make sense to a non-engineer. Providing opportunities for students to write about new ideas may promote a deeper understanding of the material, particularly if they must write to a non-specialist audience [6,7].…”
Section: Introductionmentioning
confidence: 99%